2007
DOI: 10.1152/ajpregu.00626.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pelvic responses to stressors in female CRF-overexpressing mice

Abstract: Acute stress affects gut functions through the activation of corticotropin-releasing factor (CRF) receptors. The impact of acute stress on pelvic viscera in the context of chronic stress is not well characterized. We investigated the colonic, urinary, and locomotor responses monitored as fecal pellet output (FPO), urine voiding, and ambulatory activity, respectively, in female and male CRF-overexpressing (CRF-OE) mice, a chronic stress model, and their wild-type littermates (WTL). Female CRF-OE mice, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 79 publications
(133 reference statements)
1
49
1
Order By: Relevance
“…Astressin B selectively blocked the initial robust stress-induced response without affecting the later lower response. Similar blockade by astressin B of the initial high colonic motor response to stress, without affecting the subsequent basal like response, are well documented (28,35). The evidence that astressin does not have effect on basal colonic motor activity (28, 34 -36), coupled with the present data in which astressin B blocked the initial robust response without affecting the subsequent 20-to 60-min period response, suggests that the later non-astressin B-sensitive low and stable contractile pattern may represent a basal type of activity.…”
Section: Validity Of Solid-state Manometry For Conscious Mouse Colon mentioning
confidence: 56%
See 3 more Smart Citations
“…Astressin B selectively blocked the initial robust stress-induced response without affecting the later lower response. Similar blockade by astressin B of the initial high colonic motor response to stress, without affecting the subsequent basal like response, are well documented (28,35). The evidence that astressin does not have effect on basal colonic motor activity (28, 34 -36), coupled with the present data in which astressin B blocked the initial robust response without affecting the subsequent 20-to 60-min period response, suggests that the later non-astressin B-sensitive low and stable contractile pattern may represent a basal type of activity.…”
Section: Validity Of Solid-state Manometry For Conscious Mouse Colon mentioning
confidence: 56%
“…Previous studies have shown that over 80% of the fecal pellet output response to acute stress occurs in the first 30 min of the stress sessions (28,34,35). In the present study setting, colonic contractile response was continuously recorded for 60 min.…”
Section: Association Of Colonic Contraction and Fecal Pellet Outputmentioning
confidence: 86%
See 2 more Smart Citations
“…Genetic model of depression or anxiety, such as the high-anxiety Wistar-Kyoto (WKY) rats or Flinders Sensitive Line rats have shown increased sensitivity to colorectal distension (Overstreet and Djuric 2001). In the same way genetic models deleting CRF1 exhibit a decrease in colonic sensitivity to colonic distension (Trimble, et al 2007) while models overexpressing CRF1 exhibit enhanced response to colonic distension (Million, et al 2007). These data argue for the filiation stress-anxietyinflammation and visceral hypersensitivity.…”
Section: Stress Effect On Visceral Sensitivitymentioning
confidence: 99%